Corrosion Performance of Steel Embedded in Activated Fly Ash Concrete - George, Sunilaa; Thenmozhi, R.; Magudeswaran, P. N. (Techniques and Innovation in Engineering Research Vol. 9, 2023)
Cement concrete is the most common construction material used in infrastructure projects because of its versatility. Fly ash is one among the commonly used mineral admixtures as it is available in large quantities in many developing countries. The Ministry of Power, Government of India, estimates that 600 million tons of fly ash will be generated from thermal power plants by 2031-2032, which is a major concern for the environment. The use of fly ash as a building material is largely determined by its mineral structure and pozzalonic property. Different methods of activation can improve these two properties of fly ash. This paper focuses on the chemical activation of fly ash with CaO and Na2SiO3, and the corrosion potential of chemically activated fly ash concrete against corrosive environments is demonstrated by acid resistance tests, impressed voltage studies, and permeability studies.